Development of an instrument evaluating the impact of surgeon-patient relationship in patients on sick leave - Thierry Dubert; Cedric Girault; Alexandre Kilink; Marc Rozenblat; Yves Lebellec; Anne-Lise Vataire; Myriam Vilasco; Gregory Katz (Journal of Market Access & Health Policy)
Background: To date, no specific instruments exist to measure the quality of the patient-surgeon relationship despite its potential to influence clinical and economic outcomes in patients undergoing surgery for musculoskeletal disorders (MSDs). Objective: The objective was to develop and validate an instrument to assess the quality of the patient-surgeon relationship, taking into account the return to work after functional restoration surgery. Methods: The instrument development was based on literature review, cognitive interviews and expert examinations. The instrument’s psychometric properties were explored in a sample of 50 French patients on sick leave with musculoskeletal disorders or hand injuries. Face validity, internal consistency and test-retest reliability were evaluated. The dimensionality of the instrument was studied using an exploratory principal component analysis. Results: The 11-item instrument showed good psychometric properties. The cognitive interviews allowed enhancing the validity of the instrument content by capturing patients’ point of view. The exploratory principal component analysis demonstrated the uni-dimensionality of the instrument with the first factor accounting for 83% of the total explained variance. Conclusion:This study has developed the first instrument capable of the specific assessment of the impact of the surgeon-patient relationship on recovery, in patients with hand traumas and MSDs.